'Iddah in the View of Islam and Feminists - Hilal, Syamsul; Harahap, Sumper Mulia (al-'adalah, 2021)
This study examines Islamic concepts of 'Iddah (waiting period for a divorced wife) and how the Feminists view it. The aim is to comprehend the different perspectives and try to put the problem in the right position. This research is purely library research using a socio-philosophical approach. Data were obtained from literature, books, and available documents. Based on the results of the study, it can be concluded that in Islamic teachings 'iddah is intended to determine the status of the womb, whether pregnant or not, to avoid mixing the lineage of the expecting baby. This is different from the view of the feminists who think that the provision regarding 'iddah is a product of a patriarchal culture that marginalizes women as it only applies to women, and not to men. This feminist view is based on the spirit of equality before the law which demands equal rights and obligations. The view, however, needs to be reviewed as the provision of 'iddah does not necessarily mean ignoring the principle of equality between men and women. Men and women by nature are created with different physical and emotional characters according to their respective roles. Even if such a view is applied, new problems will arise and damage the order of human culture universally